“Haec Ecclesia… subsistit in Ecclesia catholica” (LG 8): the subsistence of the Church of Christ as a starting point toward Catholic unity - Derpich, Nikola (Alpha omega, 2018)
In the documents of the Second Vatican Council a deliberated exact expression is found that seeks to affirm the unity and singularity of the Church while respecting the elements of truth and sanctification found in every Christian confession: the Church of Christ subsists in the Catholic Church (cf. Lumen Gentium, 8). The goal of this inquiry is to consider the clarifications intended by the expression subsistit in, including its theological and philosophical meaning. It considers: the conciliar process of formulating the expression; its post-Conciliar reception; ulterior Magisterial clarifications regarding its interpretation; its theological contribution to understanding the relationship between Christian confessions, Church unity, and Church catholicity; and it’s suitability for ecumenical dialogue at the theological level. Sommario: Nei documenti del Vaticano II troviamo una espressione ponderata e precisa con la finalità di affermare la unità e unicità della Chiesa e di rispettare gli elementi di santificazione e di verità che si trovano in ogni confessione cristiana: la Chiesa di Cristo sussiste nella Chiesa Cattolica (cf. Lumen Gentium, 8). Nello studio ci proponiamo di considerare le precisazioni su cosa si intende con questa espressione, compreso il valore filosofico e teologico del termine subsistere. Prenderemo in considerazione l’iter della sua formulazione conciliare; la recezione post-conciliare della medesima e le ulteriori precisazioni sulla sua interpretazione; il contributo teologico della espressione alla comprensione del rapporto tra le confessioni cristiane, l’unità della Chiesa, e la cattolicità della Chiesa; e la sua adeguatezza per il dialogo ecumenico a livello teologico.